Developing a trapping assay to assess the viability of Trogodermavariabileas a behavioral surrogate species for the biosecurity threat, Trogodermagranarium(Coleoptera: Dermestidae) - Burr, Ryan; Morrison, William R., III; Arthur, Frank; Domingue, Michael (My University, 2017)
The Khapra beetle (KB), Trogoderma granarium, is a pest that threatens the biosecurity of the United States. This species has not established itself in this country, however in the past few years there has been an alarming increase in the number of interceptions of adults at borders and ports in the U.S. Because researchers in the U.S. are only able to work with KB in specially designated APHIS quarantine facilities, understanding the full extent of the threat from this species would proceed much faster if a behavioral surrogate species could be used that was already widespread in the country. One potential surrogate species is Trogodermavariabile, the warehouse beetle (Fig. 1), which is closely related to KB, occurs throughout the U.S., and is a destructive pest of stored products in its own right.